PENGEMBANGAN KIT ELEKTROKIMIA KELAS XII SMA - JUWITA, RATULANI (STKIP PGRI Sumatera Barat, 2015)
Learning media is a very important factor in the learning process. In the framework of the provision of instructional media for teaching high school chemistry Electrochemistry Kit developed for the implementation of experiments in the classroom. Therefore, this study aimed to develop chemistry learning media in the form of Electrochemistry Kit SMA valid, practical and effective. This type of research is the development of research using patterns of development Gustafson & Branch. This development model to apply the principles of systems approach that consists of five stages: analysis, design, development, evaluation, and implementation. In this study, learning media created just developed to the stage of development. Phase analysis, which analyzes the curriculum and student analysis. At the design stage to design instructional media. Whereas at this stage of development, the design of learning tools that have been designed and then validated by 2 validator field of chemistry and the first person in the field of educational evaluation validator. Media that has been revised based on suggestions and corrections validator then tested on a limited basis to the 31 students of class XI IPA1 SMAN 1 Gunung Talang in Solok regency of West Sumatera. The trial aims to look at the practicalities of learning tools that have been developed, whereas the observed effectiveness is student learning outcomes. Analysis of the data used is qualitative descriptive statistics to validate learning media by the validator, as well as the practicalities of learning media by teachers and students. Based on an assessment of the validator, Electrochemistry Kit categorized as invalid. While the practicalities value is based on observations of teacher and student responses categorized as practical. The effectiveness of cognitive learning outcomes of students in both categories with classical completeness above 90%. The conclusion from this study is the high school class XII Electrochemistry Kit developed is valid, practical, and effective on competency standards applying the concept of oxidation-reduction reactions and electrochemistry in technology and everyday life. Keywords: KIT, Validity, practicalities, Effectiveness. AbstrakMedia pembelajaran merupakan faktor yang sangat penting dalam proses pembelajaran. Dalam rangka penyediaan media pembelajaran untuk pembelajaran kimia SMA dikembangkan Kit Elektrokimia untuk pelaksanaan percobaan di dalam kelas. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan media pembelajaran kimia berupa Kit Elektrokimia SMA yang valid, praktis dan efektif. Jenis penelitian adalah penelitian pengembangan dengan menggunakan pola pengembangan Gustafson & Branch. Model pengembangan ini menerapkan prinsip-prinsip pendekatan sistem yang terdiri dari lima tahapan, yaitu analisis, perancangan, pengembangan, evaluasi, dan implementasi . Pada penelitian ini, media pembelajaran yang dibuat hanya dikembangkan sampai tahap pengembangan. Tahap analisis, yaitu menganalisis kurikulum dan analisis siswa. Pada tahap perancangan dilakukan perancangan media pembelajaran. Sedangkan pada tahap pengembangan, rancangan perangkat pembelajaran yang telah dirancang kemudian divalidasi oleh 2 orang validator dibidang ilmu kimia dan 1 orang validator dibidang evaluasi pendidikan. Media pembelajaran yang telah direvisi berdasarkan saran dan koreksi validator kemudian diujicobakan secara terbatas pada 31 orang siswa kelas XI IPA1 SMAN 1 Gunung Talang Kabupaten Solok Sumatera Barat. Uji coba bertujuan untuk melihat praktikalitas perangkat pembelajaran yang telah dikembangkan, sedangkan efektivitas yang diamati adalah hasil belajar siswa. Analisis data yang digunakan adalah statistik deskriptif kualitatif untuk memvalidasi media pembelajaran oleh validator, serta praktikalitas media pembelajaran oleh guru dan siswa. Berdasarkan penilaian dari validator, Kit Elektrokimia dikategorikan valid. Sementara nilai praktikalitas berdasarkan pengamatan respon guru dan siswa dikategorikan praktis. Efektivitas dari hasil belajar ranah kognitif siswa dalam kategori baik dengan ketuntasan klasikal di atas 90 %. Kesimpulan dari penelitian ini adalah Kit Elektrokimia kelas XII SMA yang dikembangkan sudah valid, praktis, dan efektif pada standar kompetensi menerapkan konsep reaksi oksidasi-reduksi dan elektrokimia dalam teknologi dan kehidupan sehari-hari. Kata kunci: KIT, Validitas, Praktikalitas,efektivitas